(untitled) (Faridpur Medical College Journal, 2019)
This Study was done to assess safety and feasibility of non-descent vaginal hysterectomy for benign gynecological disease. A prospective observational study was conducted over a sample size of 50 patients at the department of Obstetrics and Gynecology of Faridpur Medical College Hospital from 1st January 2017 to 31st December 2017. All patients requiring hysterectomy for benign gynecological disorders who did not have any uterine descent were recruited for this study. Non-descent vaginal hysterectomy was performed in cases where uterus was mobile with size not exceeding 16 weeks gestation and with adequate vaginal access. Morcellation techniques like bisection, myomectomy, wedge debulking or combinations of these were employed in bigger sized uterus. A total of 50 cases were selected for non-descent vaginal hysterectomy. Among these, 47 cases successfully underwent non-descent vaginal hysterectomy. Majority (44%) of the patients were in age group of 41-45 years. All patients were parous. Uterine size was <10 wks in 30 cases and >10 wks in 20 cases. Commonest indication was leiomyoma of uterus (46%). Mean duration of surgery was two hours. Mean blood loss was 200 ml. Reasons for failure to perform nondescent vaginal hysterectomy was difficulty in opening pouch of douglus in two cases because of adhesions and in one case there was difficulty in reaching the fundal myoma which prevented the uterine descent. The most common complication was post-operative pain in 22% of cases. Febrile morbidity was present in 4% of cases. Blood transfusion was required in 7 cases. Average duration of hospital stay was three days. Vaginal hysterectomy for benign gynecological causes other than prolapse safe, feasible and patient friendly. Faridpur Med. Coll. J. Jul 2018;13(2): 89-92